Effects of 1-methylcyclopropene and modified atmosphere packaging on fruit quality and superficial scald in Yali pears during storage - Yun-xiao FENG; Yu-dou CHENG; Jin-gang HE; Li-mei LI; Jun-feng GUAN (Journal of Integrative Agriculture, 2018)
The Yali pear (Pyrus bretschneideri Rehd.) is susceptible to superficial scald during prolonged cold storage and at shelf life. This study investigated the effects of 1-methylcyclopropene (1-MCP) and modified atmosphere packaging (MAP) on changes of fruit quality and superficial scald during cold storage and at shelf life in Yali pear. Compared with MAP, the combination of MAP and 1-MCP (MAP+1-MCP) treatment reduced the carbon dioxide and ethylene content inside the packaging bag. The 1-MCP, MAP, and MAP+1-MCP treatments reduced the superficial scald index, malondialdehyde content, O2−· production rate and relative conductivity and inhibited the accumulation of α-farnesene and conjugated trienes in the peel. 1-MCP and MAP+1-MCP treatments maintained a higher phenolic content and enhanced the catalase and superoxide dismutase activities in the fruit, while reduced activities of lipoxygenase and polyphenol oxidase in the peel preceding the onset of superficial scald. Comprehensive analysis indicated that the MAP+1-MCP treatment is the most effective method tested for improving the quality of Yali pears during cold storage and at shelf life.